Education quality for future doctors: a case study of the introduction of an Education Quality Dashboard (EQD) in a UK teaching hospital. (28th October 2018) - Carr, Sue; Kirtley, Joanne; Shaw, Liz; Willars, Janet; Tarrant, Carolyn
Summary: Background: The quality of postgraduate training environments vary, but measures of the quality of training environments are lacking. This case study describes the use of management principles combined with educational expertise to facilitate the development and evaluation of an Education Quality Dashboard (EQD) for monitoring the quality of training in a large UK NHS teaching hospital. Methods: Evaluation was conducted through the inspection of data‐reporting trends and interviews with key stakeholders. Fourteen key stakeholders took part in semi‐structured interviews about their experiences of implementing the EQD. Data were analysed thematically usingnvivo 10. Results: The introduction of the EQD drove improvements in completeness of data about education standards, and improvements in performance on key metrics. Interviewees suggested that the EQD was feasible to compile but required infrastructure for data collection to be established and maintained. The use of a dashboard format was seen as helping to raise the profile of education quality standards in the trust, particularly at the board level, although some limitations of the dashboard were noted. The EQD enabled proactive monitoring and managing of problems with the educational environment, and interviewees identified concrete improvements that had resulted from the use of the dashboard. Making the EQD work well required commitment and leadership from senior staff. Feeding back and acting on findings was seen as critical for continuing engagement. Discussion: The dashboard is now embedded as part of routine practice across the hospital, and has the potential to be implemented nationally to help drive improvements in the quality of education provision.